Sosialisasi Pemanfaatan Sumber Visual Dalam Penelitian Sejarah Bagi Mahasiswa S1 Sejarah Fakultas Ilmu Budaya Universitas Diponegoro - Daradjati, Keke Pahlevi; Handayani, Tri (Departemen Linguistik, Fakultas Ilmu Budaya Universitas Diponegoro, 2025)
This workshop on the use of visual sources in historical research aims to address the critical need for students to go beyond conventional textual sources and explore the potential of visual sources in constructing historical narratives. By introducing the significance, types, and application of visual sources through case studies of historical event reconstruction—especially when textual sources are limited—this activity is designed to equip students with the theoretical knowledge and practical skills necessary to effectively integrate visual sources into their research projects.